Respuesta :

Answer:

There is no solution.

Step-by-step explanation:

There is no solution.

Substitute the value of y into the second equation:

3(2/3x + 6) - 2x = 0

2. Multiply and simplify the expression:

2x + 18 - 2x = 0

3. Combine like terms.

18 ≠ 0

Hence, there is no solution.

Hope this helped ! :)

Y=2/3x+6
3y-2x=0
First making equations
3y=2x+6 (cross multiplication of y*3)
3y-2x=6 equation 1
3y-2x=0 equation 2
Add equation1 from 2 we get,
3y-2x=6

3y-2x=0
(-) (+). =(-)
_______
0 = 6
Thus the valve cannot be obtained